Random oscillations in the Van der Pol system under the action of a broadband random process - Mitropolskiy, Yu. A.; Nguen, Dyk Tin; Nguyen, Dong An (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We construct the second approximation for random oscillations described by the Van der Pol equation which are under the action of a broadband random process.